DRAMATIC DANCE WORK WITH THE TITLE "WREDAYA" AS A VISUALIZATION OF MBAH KARTINING'S SPIRIT OF STRUGGLE - Rizky Pratama, Fairuz Ahmad; Dwi Sasanadjati, Jajuk (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
The Muludan Mask tradition is a tradition to welcome the Prophet's birthday, but unfortunately it is starting to fade due to the influence of globalization & modernization. Mbah Kartining, the remaining Muludan Mask craftsman, remains loyal and continues to be enthusiastic about maintaining the existence of the Muludan Mask. The purpose of creating this dance work is to visualize the spirit of Mbah Kartining's struggle in preserving & maintaining the Muludan Mask tradition. Made using Jacqueline Smith's I construction method. The Wredaya dance work is a dance work with the theme of the spirit of struggle, inspired by Mbah Kartining's spirit in maintaining the Muludan Mask in the era of globalization & modernization which continues to accelerate, packaged in the form of a dramatic dance type with double cones, presented by 9 female dancers, with a presentation mode representative-symbolic, the East Javanese style of the Arek ethnic group. dressed in a kutung kebaya and shorts, dominated by green and gold which symbolizes the ever-growing enthusiasm to achieve glory from Mbah Kartining's hope of maintaining this tradition until it grows again. Staged on the Proscenium stage which is supported by lighting. Accompanied by two types of musical instruments, namely Javanese gamelan with pentatonic tones and western music with diatonic tones.